Creation of Warehouse Models for Different Layout Designs - Köhler, Mirko; Lukić, Ivica; Nenadić, Krešimir (International Journal of Electrical and Computer Engineering Systems, 2014)
Warehouse is one of the most important components in logistics of the supply chain network. Efficiency of warehouse operations is influenced by many different factors. One of the key factors is the racks layout configuration. A warehouse with good racks layout may significantly reduce the cost of warehouse servicing. The objective of this paper is to give a scheme for building warehouses models with one-block and two-block layout for future research in warehouse optimization. An algorithm for creating a model database of a warehouse is introduced.